9=6(q-6)

Simple and best practice solution for 9=6(q-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9=6(q-6) equation:


Simplifying
9 = 6(q + -6)

Reorder the terms:
9 = 6(-6 + q)
9 = (-6 * 6 + q * 6)
9 = (-36 + 6q)

Solving
9 = -36 + 6q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-6q' to each side of the equation.
9 + -6q = -36 + 6q + -6q

Combine like terms: 6q + -6q = 0
9 + -6q = -36 + 0
9 + -6q = -36

Add '-9' to each side of the equation.
9 + -9 + -6q = -36 + -9

Combine like terms: 9 + -9 = 0
0 + -6q = -36 + -9
-6q = -36 + -9

Combine like terms: -36 + -9 = -45
-6q = -45

Divide each side by '-6'.
q = 7.5

Simplifying
q = 7.5

See similar equations:

| 0=-0.09+1.1x | | 7x-2(4x+23)+12= | | 5+7=2x | | -6(-3)-7(2)=4 | | 2(y+5)-4y=16 | | 3n-n+5= | | 5+2(2x-5)=-2+3(x-2) | | 2x-5x=-1-5 | | -4x-8=3x-17 | | 750+30x=y | | -9(a+6)=2 | | y=-3.3x-3.3 | | x+x+11=37 | | 2(2x+1)+x=-39 | | y=-2x^2-24x-20 | | -9=m-98 | | Y^2+21y=0 | | 13=-7+r | | 4x-35=25 | | -1(x+3)=2x-12 | | -3(6-5x)=27 | | -8(p-9)=6 | | 32+4n=96 | | (x*8)-(x*3)=60 | | -6.3-2.3b=26.13 | | 56x+8y=24 | | 5+7y=82 | | -3(j+4)=8 | | f+4=11 | | y=0.25x^2(x^2-6) | | 5(z-2)=7 | | 4(2x+1)=27 |

Equations solver categories